Intensity of Mystical Experiences Occasioned by 5-MeO-DMT and Comparison With a Prior Psilocybin Study - Barsuglia, Joseph; Davis, Alan K.; Palmer, Robert; Lancelotta, Rafael; Windham-Herman, Austin-Marley; Peterson, Kristel; Polanco, Martin; Grant, Robert; Griffiths, Roland R. (Frontiers in Psychology, 2018)
5-MeO-DMT is a psychoactive substance found in high concentrations in the bufotoxin of the Colorado River Toad. Emerging evidence suggests that vaporized 5-MeO-DMT may occasion mystical experiences of comparable intensity to those occasioned by more widely studied psychedelics such as psilocybin, but no empirical study has tested this hypothesis. Data was obtained from 20 individuals (mean age = 38.9, male = 55%, Caucasian = 85%) who were administered 5-MeO-DMT as part of a psychospiritual retreat program in Mexico. All participants received 50mg of inhaled vaporized toad bufotoxin which contains 5-MeO-DMT and completed the Mystical Experience Questionnaire (MEQ30) approximately 4-6 hours after their session. Administration of 5-MeO-DMT occasioned strong mystical experiences (MEQ30 Overall Mintensity = 4.17, ± 0.64, range 0–5) and the majority (75%) had “a complete mystical experience” (≥60% on all MEQ30 subscales). Compared to a prior laboratory-based psilocybin study, there were no differences in the intensity of mystical effects between 5-MeO-DMT and a high dose (30 mg/70 kg) of psilocybin, but the intensity of mystical effects was significantly higher in the 5-MeO-DMT sample compared to moderate/high dose (20 mg/70 kg) of psilocybin (MEQ30 Total Score: p = .02, d = 0.81). Administration of vaporized 5-MeO-DMT reliably occasioned mystical experiences in a majority of individuals and was similar in intensity to high dose psilocybin administered in a laboratory setting. The short duration of action may be advantageous for clinical interventions and for studying mystical-type experiences.